DRINKING WATER SUPPLY UNDER THE CONDITIONS OF MASS DEVELOPMENT OF BLUE-GREEN ALGAE IN RESERVOIRS - Ksenia V. Bespalova; Aleksandra V. Selezneva; Vladimir. A. Seleznev (Водное хозяйство России: проблемы, технологии, управление)
An assessment of the pollution of a surface source of water supply (the Kuibyshev reservoir) with metabolites of cyanobacteria (blue-green algae) under conditions of an increase in biogenic load is carried out. During the period of mass development of cyanobacteria, the quality of water in the reservoir deteriorates in terms of a number of indicators, including smell, taste, and content of organic and toxic substances. Among the wide range of cyanoxins, the greatest danger to the population is microcystin-LR, the concentration of which in drinking water should not exceed 1 μg/dm3. The growth of anthropogenic load and global warming of the climate create favorable conditions for the rapid development of cyanobacteria, therefore, the problem of providing the population with high-quality drinking water will only worsen in the future. Traditional methods used at drinking water treatment plants in Volga cities are ineffective in removing intracellular and extracellular cyanotoxins. The best and safest barrier against the ingress of cyanotoxins into drinking water can be membrane technologies that allow ultrafiltration of bacterial cells without mechanical damage and nanofiltration of cyanotoxins dissolved in water.